Efficient Nitrogen Management for Reducing Weed Population and Improving Productivity of Boro Rice - Md. Hasan Miah; Sinthia Afsana Kheya; Mahfuza Begum; Md. Omar Ali; Most. Mohoshena Aktar; Md. Abdus Salam (Fundamental and Applied Agriculture, 2024)
Among many causes of weed growth and rice's low yield, improper nitrogen management are thought to be an important issue. An experiment was conducted from December 2021 to June 2022 at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh. Five different nitrogen management and six different weed control techniques were applied to BRRI dhan29. Four of the thirteen weed species were grasses, three were broadleaf, four were sedges and two were aquatic. N1W0 (100% N from urea × un-weeded control) had the greatest weed density and dry weight (78.67 m-2 and 4.80 g m-2) at 20 DAT, whereas 100% N from USG × weed free over the time (N4W1) treatment had the lowest weed density and dry weight (0.00 m-2 and 0.00 g m-2). When 100% N from USG was applied coupled with weed-free conditions the maximum numbers of effective tillers hill-1, grains panicle-1, straw yield, and biological yield were 10.11, 122, 6.23 t ha-1, and 11.07 t ha-1, respectively. The minimum effective tillers hill-1, grains panicle-1, straw yield and, biological yield was 6, 70.84, 3.13 t ha-1 and, 4.95 t ha-1, respectively found at 0 kg ‘N' ha-1 followed by un-weeded control. The maximum grain yield was 5.84 t ha-1 for 100% "N" from USG and weed-free conditions, while the lowest grain yield was 2.15 t ha-1 for 0 kg "N" ha-1 and un-weeded control. However, because of the labor problem and the weeds' tremendous capacity for regeneration, it is impossible to keep the field weed-free over the whole growing season. This study showed that farmers may choose to apply 100% N from USG in combination with either pre-emergence herbicide and hand weeding at 30 DAT or early post-emergence herbicide and hand weeding at 30 DAT to effectively manage weeds and maximize grain yield in boro rice. [Fundam Appl Agric 2024; 9(4.000): 256-265]